2010
DOI: 10.1260/1747-9541.5.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Training Characteristics of Male Junior Cross Country and Track Runners on European Top Level

Abstract: The purpose of the present study was to describe training characteristics of distance junior runners at European top level. INTRODUCTIONThe question of how to organize daily training to improve aerobic capacity in elite junior endurance athletes is a debated topic among coaches and researchers throughout the world, and several attempts have been made to construct a model of optimal endurance training 1,2 . In a training program for long-distance runners, the most essential exercise variables are training volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(62 citation statements)
references
References 39 publications
0
53
0
Order By: Relevance
“…Calculations on the training reported in the diaries was used to estimate: a) average number of training sessions during the preparation period (November -February), the precompetition period (March and April) and the competition season (May -September) 22,34,35 ; b) average training volume (km/week); c) distribution of training at the prescribed intensities (% of HR max ); and d) number of weekly sprints/strides and strength training workouts.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Calculations on the training reported in the diaries was used to estimate: a) average number of training sessions during the preparation period (November -February), the precompetition period (March and April) and the competition season (May -September) 22,34,35 ; b) average training volume (km/week); c) distribution of training at the prescribed intensities (% of HR max ); and d) number of weekly sprints/strides and strength training workouts.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have shown significant improvements in V · O 2 max and running speed at anaerobic threshold (vAT) in elite endurance athletes using the anaerobic threshold training model (80-87% of V · O 2 max/ 82-92% of HR max ) [21][22][23] . Indeed, the runners with greatest success, the Kenyan runners, do a lot of training at this intensity 24,25 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these training prescription variables, the way in which athletes distribute their training across the training intensity spectrum (i.e., training intensity distribution; TID) is considered to be a key determinant of training and performance adaptations. [1][2][3][4][5] Training intensity can be measured via external work rate (running speed or power output), 6,7 an internal physiological response (i.e., heart rate or VO2), 8,9 or by how the training is perceived (i.e., rating of perceived exertion; RPE). 10 To further guide training prescription and monitoring, training intensity zones have been employed, and while there is not yet a consensus on the most appropriate training zone model, models with up to 7 training zones have been described.…”
Section: Introductionmentioning
confidence: 99%